The effect of body mass index and anxiety status on blood pressure in patients admitted to family medicine outpatient clinic - Orhan Ayan; Ahmet Yılmaz; Ahmet Dündar; Mahir Kuyumcu; Vasfiye Demir Pervane (SERNEV, 2022)
Introduction: Hypertension is a global public health problem that is the leading cause of preventable death in the world and a disease which can cause many morbidities and mortality if not controlled or treated effectively. In many studies, it has been determined that anxiety and body mass index(BMI) are among the factors affecting hypertension. However, different results have been obtained in many studies in terms of the relationship between anxiety and hypertension. This study was carried out with the aim to evaluate the effect of body mass index and anxiety on blood pressure and the factors affecting blood pressure in patients who applied to outpatient clinic of family medicine at Dicle University Faculty of Medicine.Methods: 403 patients aged between 18- 65 years, who applied to outpatient clinic of family medicine at Dicle University Faculty of Medicine between 01.04.2018 and 01.07.2018, were included in this cross-sectional study. The population of the study was the province where the study was carried out, and the sample size was calculated with a power of 80%. The patients' body mass index and anxiety scores from Beck anxiety scale were calculated and measurements of arterial blood pressure were performed. The relationship between BMI, Beck anxiety scores and blood pressure of patients were investigated.Results: Of the participants, 50.1% were male, 49.9% were female and the average age was 34.11 in years. Of the patients, the mean BMI as 25.52 kg/m², the mean anxiety score as 7.40 and the arterial blood pressures as 117.80/75.54 mmHg were measured. It was found that arterial blood pressure raised significantly as the BMI group increased. While the relationship between the severity of anxiety and systolic blood pressure was significant, its relationship with diastolic blood pressure was not significant. There was a positive correlation between BMI, anxiety score and systolic and diastolic blood pressure.Conclusions: According to the results of this study, it was found that the increase in BMI and Beck anxiety scores may be related with increase in arterial blood pressure. This result showed that common health problems in primary care such as anxiety, obesity and hypertension may be associated with each other, and it can be effectively fought against hypertension and its complications with the perspective of family medicine and biopsychosocial approach.Keywords: Anxiety, Hypertension, Blood Pressure, Obesity, Body Mass Index